Pecan production improvement by zinc under drip irrigation in calcareous soils - Olivas-Tarango, Ana Luisa; Tarango-Rivero, Socorro Héctor; Ávila-Quezada, Graciela Dolores (REVISTA TERRA LATINOAMERICANA, 2021)
Pecan trees demand a considerable amount of zinc (Zn) for the activity of Zn-dependent enzymes involved in the metabolism of proteins, sugars, carbohydrates, and auxins. Thus, the aim of this study was to evaluate the production of pecan trees with an edaphic contribution of 12 to 15 kg ha-1 of chelated zinc through drip irrigation, including the addition of a commercial microbial consortium, throughout a three-year study. The control treatment was the conventional fertilization management using foliar zinc. The methodology proposed in this study allowed to obtain an additional kg of nut per tree after three years. With the control treatment, the shoot (21 vs. 20.1 cm) and leaf (39 vs. 36.8 cm2) grew slightly better than the foliar zinc treatment, and promoted the enrichment of microbial communities in the rhizospheric soil, as well as an ectomycorrhizal colonization of 69.9%. In addition, the chelated zinc treatment applied in drip irrigation avoided night-time spraying, therefore, this management in pecan orchards offers producers an economic, ecological and sustainable option that allows them to improve yield.